AUTENTISITAS SUMBER SEJARAH PANCASILA DALAM MASA SIDANG PERTAMA BADAN UNTUK MENYELIDIKI USAHA-USAHA PERSIAPAN KEMERDEKAAN TANGGAL 29 MEI-1 JUNI 1945 - Hardinanto, Aris (Veritas et Justitia, 2017)
This article seeks to compares different ideas concerning Indonesian statehood as put forth by our founding father in sessions of the Dokuritsu Zyunbi Tyosa Kai (Investigating Body for Preparing Indonesia's Independence). The author notes that there is doubt as of the authenticity of documents recording the debates and the speeches made during meetings held by this body (28 may-1 June 1945 & 10 July-17 July 1945).  On one side, there is the preparatory documents of the 1945 Constitution as issued by Muhammad Yamin and which is regarded by the State Secretariat as the one and only authentic source (from 1959-1992).  On the other hand, notes collected by Pringgodigdo and Yamin was latter used as the basis for the publication of the Body’s minutes of meetings in 1995.  The author observes that both collections (Yamin and Pringodidgo) differs in its exposure of ideas on the Indonesian statehood put forth during the Body’s meetings.